Penanggulangan Miskonsepsi Menggunakan Pendekatan Konflik Kognitif - Sapuadi Sapuadi; Muhammad Nasir (Al-Mudarris, 2020)
This article is a conceptual study of the cognitive conflict approach as an alternative to changing student misconceptions in the learning process. The cognitive conflict approach is based on Piaget's theory of cognitive development, especially about equilibration. The study was conducted through a research library. This study discusses misconceptions and their causes, Piaget's theory of cognitive development as the basis for changing student concepts, and cognitive conflict approaches to overcome student misconceptions.